The Effectiveness of Scientific Creativity-Based Teaching Factory in Improving Vocational Students’ Soft Skills: A Mixed Methods Approach in Renewable Energy Engineering - Pathan, Pathan; Alaydrus, Kadir Alpan (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2026)
This study aimed to examine the effectiveness of scientific creativity-based Teaching Factory in improving vocational students’ soft skills in the Renewable Energy Engineering Program. The study employed a sequential explanatory mixed methods design with a quasi-experimental pretest-posttest control group design. The participants were 44 Grade XI students, consisting of 22 students in the experimental group and 22 students in the control group. Quantitative data were collected using a soft skills scale covering communication, collaboration, problem solving, responsibility, and adaptability. Qualitative data were obtained through semi-structured interviews with students and a vocational teacher. The results showed that the experimental group’s soft skills score increased from 67.45 to 85.50, while the control group increased from 60.77 to 67.36. The experimental group achieved a moderate N-gain of 0.55, whereas the control group obtained a low N-gain of 0.15. ANCOVA indicated a significant group effect after controlling for pretest scores, F(1, 41) = 147.92, p < .001. The qualitative findings revealed that the improvement in soft skills was supported by students’ engagement in real problem identification, group work, idea communication, solar-panel lighting system testing, technical problem solving, product revision, reflection, and teacher feedback. This approach has the potential to strengthen contextual, collaborative, and workplace-oriented vocational learning, although its implementation requires adequate learning materials, practical facilities, and consistent teacher guidance at school.